2011
DOI: 10.1007/s11692-011-9122-y
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Thermal Preferences of Female Oviparous Common Lizards During Egg Retention: Insights into the Evolution of Reptilian Viviparity

Abstract: Pregnant female Zootoca vivipara select lower body temperatures than males or nonpregnant females, and this shift in the thermal preferendum is believed to be related to optimising the conditions for embryogenesis. Thus, subjecting embryos to the higher temperature selected by males and non-gravid females might have detrimental effects on embryonic development and on hatchling fitness, according to predictions of the ''maternal manipulation'' hypothesis on the evolution of viviparity. To test the role of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Particularly, the lower temperatures at higher altitudes have a negative effect on clutch development in oviparous females but can be mitigated by viviparous females (Shine 2002 ; Webb et al 2006 ). At the sampling site (> 1300 m), egg incubation time under natural conditions is not known but would be substantially longer than in our study (Rodríguez-Díaz and Braña 2011 , 2012 ). Further, hatching success for oviparous clutches was likely higher under our incubation conditions than under strictly natural settings.…”
Section: Discussionmentioning
confidence: 72%
“…Particularly, the lower temperatures at higher altitudes have a negative effect on clutch development in oviparous females but can be mitigated by viviparous females (Shine 2002 ; Webb et al 2006 ). At the sampling site (> 1300 m), egg incubation time under natural conditions is not known but would be substantially longer than in our study (Rodríguez-Díaz and Braña 2011 , 2012 ). Further, hatching success for oviparous clutches was likely higher under our incubation conditions than under strictly natural settings.…”
Section: Discussionmentioning
confidence: 72%
“…Change in thermal preferences of gravid females toward lower temperatures is probably linked to the maintenance of temperatures suitable for a successful embryonic development, in accordance with the maternal manipulation hypothesis. Therefore, this hypothesis is not incompatible with the cold‐climate hypothesis (see Rodríguez‐Díaz et al ., ), as the low temperatures selected by pregnant females would not entail an important increase in the potential incubation time (Rodríguez‐Díaz & Braña, ).…”
Section: Discussionmentioning
confidence: 99%
“…The maternal manipulation hypothesis (Shine, 1995;Webb et al, 2006) posits that egg retention evolves because females provide eggs with a more stable and warmer thermal environment than the external one, that is, with the optimum thermal environment for embryo development. Evidence on females changing their preferred body temperatures during pregnancy (Shine, 2006), as well as on incubation temperatures similar to those preferred by nonpregnant females having detrimental effects on embryonic development supports this hypothesis (Rodríguez-Díaz & Brañ a, 2011). On the other hand, the cold climate hypothesis (Shine, 1985(Shine, , 2002, which is not necessarily incompatible with the maternal manipulation hypothesis (Rodríguez-Díaz et al, 2010), posits that egg retention is favoured at high altitudes or latitudes, where environmental temperatures are much lower than female body temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the opportunity for gravid females to bask or otherwise thermoregulate can influence the timing of oviposition (e.g., Olsson and Shine, 1997;Shine, 2006;Telemeco et al, 2010). In addition, the temperatures at which gravid female lizards maintain themselves influence the development rate of eggs once laid, as well as their hatching success (e.g., Angilletta et al, 2000;Rodríguez-Díaz et al, 2010;Telemeco et al, 2010;Rodríguez-Díaz and Braña, 2011). Maternal thermoregulation also can affect the temperature regime (i.e., the distribution of temperatures experienced rather than the mean temperature) experienced by the eggs compared to the nest environment (e.g., Shine, 2004).…”
Section: Introductionmentioning
confidence: 99%